Assessing the impact of TNCs’ activities on developing countries - A.O. Simakhova; K.Y. Yurchuk (Економіка, управління та адміністрування, 2024)
The article analyzes the impact of TNCs on the economic growth of developing countries. The study used general scientific methods of analysis and synthesis, comparative method and method of data systematization. The information base of the study is based on scientific works of foreign and Ukrainian authors, statistical information of UNCTAD, and data from Internet resources. The geographical structure of TNCs’ activities is determined. It is found that today the largest number of TNCs among developing countries is concentrated in India and China. The positive and negative consequences of the impact of TNCs on the economies of developing countries and their social sphere are highlighted. The geographical distribution of foreign direct investment is analyzed in the context of the impact of TNC financial resources on developing countries. Foreign direct investment is a catalyst for the economic growth of developing countries, which is confirmed by the experience of a number of countries which have recently demonstrated high positive dynamics of their economic indicators and significant structural transformation in the modern course of their economies. The most striking examples in this regard are such countries as China, India, Brazil, Mexico, and others. The article suggests promising areas for strengthening the positive impact of TNCs on developing countries. The practical value of the article is that the recommendations set forth in it can be used by the management of TNCs and the government of developing countries.